Organoleptic Test on Subgrade Pineapple Fruit Leather with Different Drying Temprature - Bagas Aji Ghoni Ramadiansyah; Wendianing Putri Luketsi; Maya Sari (Agroindustrial Technology Journal, 2020)
Fruits are agricultural commodities that have high economic value. Pineapple is one of Indonesia's superior tropical fruit. Pineapple can be processed into various products such as juice, sweets, and fruit leather. Fruit leather is a kind of dried candy that can be used as a form of commercial processing on an industrial scale, shaped like a thin sheet of paper with a thickness of 2mm -3mm. Fruit leather is made from fruit flesh that has been crushed and dried. The purpose of this study was to determine the organoleptic test of 3 differences in drying temperature (60ºC, 70ºC, 80ºC) which included the aroma, taste, texture and color of the subgrade pineapple fruit leather. This study uses a completely randomized design (CRD) method. Data analysis was performed using the one-way Analysis of Variant or (ANOVA) method of analysis with Duncan's further tests. Subgrade pineapple leather with differentdrying temperature treatment that is 60ºC, 70ºC, 80ºC produces different fruit leather. The final result on fruit leather with a drying temperature of 60ºC looks smooth and not too dry. As for the temperature of 70ºC the surface texture looks a bit rough but still good. The temperature of 80ºC has a rough texture and feels dry. The highest yield was found at the treatment temperature of 60 ° C with a final value of 99.2% of the material, and the lowest value was found at the treatment temperature of 80 ° Cwith the final value of the material 98.2%. Based on the results of this study, the best treatment was obtained at a temperature of 60ºC subgrade pineapple puree. The temperature of 60 ° C in the organoleptic test is characteristic of light brown color and is preferred, the texture is chewy and somewhat preferred, the aroma and taste are preferred, and are the products most favored by panelists